The world's most popular manga dragon ball : piccolo conquers the world - Toriyama, Akira (San Francisco : VIZ Media, 2021)
With a wish on the Dragon Balls, Piccolo restores his youth, becoming more powerful than ever! Flying to the palace of the King of the World, he announces that he is the new King, and broadcasts his reign of terror on international TV!Only Tenshinhan and Goku have a chance to stop Piccolo: Tenshinhan by mastering a martial arts move that can kill the one who uses it, and Goku by drinking a magic potion that might make him stronger--or kill him too! Two heroes risk death to save the planet--and meanwhile, Yajirobe eats too much and gets sick!
VOL 13
Keywords: Dragon Ball (Television programme) Comic books, strips